KOLABORASI GURU DAN MAHASISWA DALAM PENERAPAN PEMBELAJARAN INTERAKTIF DI SDIT AL FURQAN PALANGKA RAYA DENGAN MODEL KOOPERATIF TIPE TEAM GAMES TURNAMENT - Nuril Ainularifin; Setria Utama Rizal; Eva Latriana Yuniarti (Universitas Nias Raya, 2024)
This study aims to analyse the collaboration between teachers and students in the implementation of interactive learning with Team Games Tournament (TGT) type cooperative model in class IV of Al Furqan Palangka Raya Integrated Islamic Elementary School in IPAS subject. The research method used was descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed that collaboration between teachers and students was effective through clear division of roles and intensive communication. The implementation of the Team Games Tournament model succeeded in increasing students' active involvement in learning, as well as motivating them through the elements of games and competition. In addition, students' learning outcomes also improved. However, some obstacles arose related to time management and differences in student understanding, which could be overcome by adjusting learning strategies. This study concludes that teacher-student collaboration and the use of Team Games Tournament are effective in creating interactive and meaningful learning.